Delirium: The 7th Vital Sign? - Prayce, Rita (2018)
Introduction: Delirium is an acute, transient and fluctuating neuropsychiatric syndrome that is common in medical wards, particularly in the geriatric and palliative care population.Material and Methods: We present a brief literature review of the definition, pathophysiology, aetiology, diagnosis, prevention and treatment of delirium and its social and economic impact.Results and Discussion: Delirium is under-recognized, especially by health professionals, and is associated with higher morbidity, mortality and economic burden. Moreover, the presence of delirium interferes with the evaluation and approach to other symptoms. Furthermore, it causes significant distress in patient’s families and health professionals. The best treatment for delirium is prevention which is based on multidisciplinary interventions that addresses the main risk factors. The scientific evidence for the treatment of delirium is scarce. Non-pharmacological approaches are usually the first choice, and includes environmental, behavioural and social strategies. Pharmacological options, mainly antipsychotics, are a second-line treatment used essentially to prevent self harm.Conclusion: The recognition and prevention of delirium are crucial. Health professional education and training, patient clinical monitoring and families support are mandatory. Considering the impact of delirium on patients, relatives, health services and professionals we must be more aware of delirium and, why not, make it the 7th vital sign.